Developing polyploid genotypes of Leptospermum scoparium. Issue 4 (2nd October 2019) - Bicknell, Ross; Boase, Murray; Morgan, Edmond
ABSTRACT: Leptospermum scoparium ('Mānuka') is native to New Zealand and South Eastern Australia. Throughout this range the species typically exists as a diploid. Only a single tetraploid accession has ever been reported and all the polyploid cultivars currently available are derivatives of that plant. Polyploidy in other species is known to influence vegetative and floral form, phenology and fertility. Floral diameter was therefore measured for the tetraploid L. scoparium 'Keatleyi', the triploid L. scoparium 'Martinii' and three diploid seedlings. The floral diameters of the tetraploid and triploid were significantly greater than those from diploid plants. However, the diploid flowers were also significantly different from each other, indicating that factors other than polyploidy influence this trait. Additionally, given the very limited number of polyploid clones available, methods were tested to generate more tetraploid plants for future study. Colchicine was effective at producing tetraploid seedlings with 6 mg/ml, the highest concentration tested, yielding the largest number of tetraploids. This method is now being used to generate tetraploids from a range of L. scoparium material.